The political integration of the Bukidnons in Garangan, Calinog, Iloilo - Dela Cruz, Llere Mae Toledo
This study sought to know the extent of political integration of the indigenous group, Bukidnons, in Garangan, Calinog, vis-a-vis the mainstream Filipino society. Moreover the study was done in order to present the Bukidnons' view regarding political integration., This study was exploratory in nature, which utilized the unstructured interview to gather data from the identified respondents in Garangan, Calinog. The interview was conducted on 147 respondents aging 15-65. Direct observation together with the field notes and diary were also used. The gathered data were documented on paper. For the purpose of analysis and discussion, the gathered data were organized in tables and themes. The study showed that socio-demographic factors such as educational attainment and status and rank affected the Bukidnons' willingness and receptivity to political integration. Their educational attainment affects their views on nationalism, their awareness on national identity, their participation in national and local political processes, their acceptance of present social, economic and political conditions and their views on contemporary issues and problems. Bukidnons with higher educational attainment have greater knowledge regarding the country, government and political integration as a whole. Bukidnons who are equipped with higher educational attainment are also receptive to changes whatever it would be and find solutions to the problems that may accompany. Aside from educational attainment, the study shows that Bukidnons with higher status and rank in their community are more aware of the things mentioned and they have more knowledge regarding the community and government as a whole. They want to be integrated because for them it signifies development and alleviating their standard of living. The findings of the study showed that the Bukidnons more likely wanted political integration but the problem lies on the attention given to them by the government because they are considered marginalized, living in the interior area of the Central Panay. But there is a greater possibility that political integration would be easy because there are some indicators that they would be politically integrated into the mainstream society, however it would become static if the government will not take initiative to bring them into the mainstream since as stated earlier, government plays significant role in the Bukidnons' political integration. Government's effective strategies would be encouraging Bukidnons to participate in socio-economic activities outside their barangay, appointing political authorities over them, imposing state's legal judicial system properly and establishing necessary infrastructure such as roads, electricity, schools and water system would lead a way to their integration. Roads could bridge the possibility of frequent interaction with the mainstream thus encouraging political integration. Moreover, schools are necessary because education plays a major role in the political integration of the Bukidnons.